Initiating and maintaining a recovery process – experiences of persons with dual diagnosis. Issue 3 (17th May 2018) - Skogens, Lisa; von Greiff, Ninive; Topor, Alain
Abstract : Purpose: The purpose of this paper is to investigate the internal and social factors that persons with experience from severe mental illness and alcohol and other drugs problems, and who have received treatment for these problems, describe as important for initiating and maintaining a recovery process. Design/methodology/approach: In total, 40 persons were interviewed and asked to describe factors they perceived as important for initiating and maintaining recovery. The software Nvivo was used to categorise data in internal and social factors with subcategories. Findings: There is significant variation in how recovery emerged but involved in general having a proper social situation and finding meaning in life. Initially, the majority had a marginalised situation with need of assistance with housing, employment, financial and social support. Research limitations/implications: The change process in the investigated group is interpreted as related to individual resources rather than belonging to a group defined as having "double trouble". Practical implications: The study implies that in addition to professional help to handle diagnosed problems, the group in focus also need support and interventions that address individual complex needs. Social implications: Supporting activities/peer support seem to be important for those lacking support from family. At the same time, it is important to recognise the risk of being forced into a recovery identity which might lead to worsening the situation for those who do not fit into this. Originality/value: By using the same design as in previous studies, comparisons with other groups are possible while still keeping the qualitative meaning of the investigated factors.